2001
DOI: 10.1897/1551-5028(2001)020<1740:ioapot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Aquatic Plants on the Fate of the Pyrethroid Insecticide Lambda-Cyhalothrin in Aquatic Environments

Abstract: Aquatic exposure assessments for pesticides are generally based on laboratory studies performed in water alone or water sediment systems. Although aquatic macrophytes, which include a variety of bryophytes, macroalgae, and angiosperms, can be a significant component of many aquatic ecosystems, their impact on pesticide fate is generally not included in exposure assessments. To investigate the influence of aquatic plants on the fate and behavior of the pyrethroid insecticide lambda (lambda)-cyhalothrin, two lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 21 publications
(21 reference statements)
4
57
0
Order By: Relevance
“…For example, Elodea could be sorbing malathion onto its surfaces and thus reducing water toxicity to Daphnia. However, although many highly-lipophilic insecticides with Log K OW values greater than 6.0 (e.g., pyrethroid and organochlorine insecticides) will bind rapidly to submersed macrophytes [20,21], malathion is relatively hydrophilic (Log K OW ¼ 2.3), and it remains unclear how much macrophytes will sorb this insecticide. In the aforementioned experiment by Gao et al [23], the authors found no evidence that malathion was taken up by macrophytes during the first 48 h following exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Elodea could be sorbing malathion onto its surfaces and thus reducing water toxicity to Daphnia. However, although many highly-lipophilic insecticides with Log K OW values greater than 6.0 (e.g., pyrethroid and organochlorine insecticides) will bind rapidly to submersed macrophytes [20,21], malathion is relatively hydrophilic (Log K OW ¼ 2.3), and it remains unclear how much macrophytes will sorb this insecticide. In the aforementioned experiment by Gao et al [23], the authors found no evidence that malathion was taken up by macrophytes during the first 48 h following exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, macrophytes can sorb insecticides, potentially reducing the duration and intensity of exposure experienced by aquatic taxa [18,19]. In fact, submersed macrophytes can sorb up to 90% of insecticides from the water column within 24 h, but such high sorption rates only occur for highly lipophilic compounds (i.e., Log octanolwater partition coefficient, K OW > 6.0), such as organochlorine (e.g., dichlorodiphenyltrichloroethane [DDT]) and pyrethroid (e.g., lambda-cyhalothrin) insecticides [20,21]. For less lipophilic compounds-such as the commonly applied organophosphate insecticides chlorpyrifos (Log K OW ¼ 4.81) and malathion (Log K OW ¼ 2.3)-the amount of insecticides removed from the water column by macrophytes typically ranges from 0 to 50% in a 24-h period [18,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…S-stag = single application in a stagnant system; S-stream = single application in a running system; M-stag = multiple applications in a stagnant system; M-stream = multiple applications in a running system; L-stag = prolonged constant exposure in a stagnant system; L-stream = prolonged constant exposure in a running system. but also by the distribution of the active ingredient over different environmental compartments such as sediment, organic and inorganic particulate material, aquatic plants (e.g., Hill, 1989;Brock et al, 1993;Brock, 1994, Samsøe-Petersen et al, 2001;Hand et al, 2001) and volatilisation from the water (e.g., Larkin and Tjeerdma, 2000). Initial half-life values of dissolved organophosphates and carbamates in the water of stagnant (model) ecosystems are in the order of less than 1-10 days (Crossland and Bennett, 1984;Hanazato and Yasuno, 1990;Lahr and Diallo, 1993;Crum and Brock, 1994;Tanner and Knuth, 1995;Wayland and Boag, 1995;Giddings et al, 1996).…”
Section: Application Methods and Pesticide Behaviourmentioning
confidence: 99%
“…Initial half-life values of dissolved organophosphates and carbamates in the water of stagnant (model) ecosystems are in the order of less than 1-10 days (Crossland and Bennett, 1984;Hanazato and Yasuno, 1990;Lahr and Diallo, 1993;Crum and Brock, 1994;Tanner and Knuth, 1995;Wayland and Boag, 1995;Giddings et al, 1996). In the case of pyrethroids, initial half-life in the water columns are in the order of less than 1 h to 3 days (Stephenson et al, 1986;Heinis and Knuth, 1992;Fairchild et al, 1992b;Farmer et al, 1995;Hand et al, 2001;Roessink et al, in press). Reported half-life of sediment-adsorbed pesticides is generally much longer (days to weeks) in the above-mentioned studies.…”
Section: Application Methods and Pesticide Behaviourmentioning
confidence: 99%
“…Brock et al (1992), for example, showed for chlorpyrifos that the mixing of the compound through the water column was strongly influenced by the vegetation structure in microcosms. For lambda-cyhalothrin, it has been demonstrated that different densities of macrophytes can have considerable influence on the fate and bioavailability of this compound (Hand et al 2001;Leistra et al 2003). Experiments with chlorpyrifos simulating different environmental conditions indicated that at higher water temperatures, and in combination with higher light intensities, dissipation rates increased (Van Wijngaarden et al 2005).…”
mentioning
confidence: 99%